The distinct functions of two classical arabinogalactan proteins BcMF8 and BcMF18 during pollen wall development in Brassica campestris. (9th March 2018) - Lin, Sue; Yue, Xiaoyan; Miao, Yingjing; Yu, Youjian; Dong, Heng; Huang, Li; Cao, Jiashu
Summary: Arabinogalactan proteins (AGPs) are extensively glycosylated hydroxyproline‐rich glycoproteins ubiquitous in all plant tissues and cells. AtAGP6 and AtAGP11, the only two functionally known pollen‐specific classical AGP encoding genes in Arabidopsis, are reported to have redundant functions in microspore development. BcMF18 and BcMF8 isolated from Brassica campestris are the orthologues of AtAGP6 and AtAGP11, respectively. In contrast to the functional redundancy of AtAGP6 and AtAGP11, single‐gene disruption of BcMF8 led to deformed pollen grains with abnormal intine development and ectopic aperture formation in B. campestris . Here, we further explored the action of BcMF18 and its relationship with BcMF8 . BcMF18 was specifically expressed in pollen during the late stages of microspore development. Antisense RNA transgenic lines with BcMF18 reduction resulted in aberrant pollen grains with abnormal cellulose distribution, lacking intine, cytoplasm and nuclei. Transgenic plants with repressive expression of both BcMF8 and BcMF18 showed a hybrid phenotype, expressing a mixture of the phenotypes of the single gene knockdown plant lines. In addition, we identified functional diversity between BcMF18 / BcMF8 and AtAGP6 / AtAGP11, mainly reflected by the specific contribution of BcMF18 and BcMF8 to pollen wall formation. These results suggest that, unlike the orthologous genes AtAGP6 and AtAGP11 in Arabidopsis, BcMF18 and BcMF8 are both integral to pollen biogenesis in B. campestris, acting through independent pathways during microspore development. Significance Statement: Arabinogalactan proteins (AGPs) are cell wall‐associated glycoproteins which have been identified to be implicated in microspore development. The findings of our manuscript show that unlike AtAGP6 and AtAGP11 which have redundant functions in Arabidopsis, their orthologous genes BcMF18 and BcMF8 in Brassica campestris are both integral to pollen biogenesis, acting through independent pathways during pollen wall development, suggesting an essential and diversified role for BcMF8 and BcMF18 in microspore development.